2019
DOI: 10.1371/journal.pbio.3000382
|View full text |Cite
|
Sign up to set email alerts
|

LATS1/2 suppress NFκB and aberrant EMT initiation to permit pancreatic progenitor differentiation

Abstract: The Hippo pathway directs cell differentiation during organogenesis, in part by restricting proliferation. How Hippo signaling maintains a proliferation-differentiation balance in developing tissues via distinct molecular targets is only beginning to be understood. Our study makes the unexpected finding that Hippo suppresses nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB) signaling in pancreatic progenitors to permit cell differentiation and epithelial morphogenesis. We find that pancreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 115 publications
1
28
0
Order By: Relevance
“…Epithelial cells undergo various biochemical changes, including the loss of epithelial characteristics and the acquisition of mesenchymal properties (11)(12). The characteristic changes in EMT are the loss of epithelial marker E-cadherin and the increase in mesenchymal markers vimentin and N-cadherin (34,36). Recently, it was revealed that downregulation of Girdin suppressed breast cancer and neuroglioma migration and invasion in vitro and that Girdin may interact with the epithelial marker E-cadherin to regulate cell-cell adhesion (24,26,37).…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial cells undergo various biochemical changes, including the loss of epithelial characteristics and the acquisition of mesenchymal properties (11)(12). The characteristic changes in EMT are the loss of epithelial marker E-cadherin and the increase in mesenchymal markers vimentin and N-cadherin (34,36). Recently, it was revealed that downregulation of Girdin suppressed breast cancer and neuroglioma migration and invasion in vitro and that Girdin may interact with the epithelial marker E-cadherin to regulate cell-cell adhesion (24,26,37).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor (TNF) binds to related receptors, predominantly activating I-κB kinase to allow the translocation of NF-κB into the cell nucleus and induce target gene expression (Yang et al, 2020). Braitsch et al (2019) confirmed that the deletion of large tumor suppressor kinases 1 and 2 (LATS1/2) led to NF-κB activation and EMT, which was accompanied by upregulated T-1 expression and ultimately promoted cell migration and invasion. Insulin-like growth factor binding protein-related protein-1 (IGFBP-rP1) was found to be up-regulated in CRC patients with lymph node metastasis CRC patients, who also exhibit up-regulated levels of T-1 (Ruan et al, 2010).…”
Section: Nf-κb Signaling Pathwaymentioning
confidence: 93%
“…We have previously reported that increased DNA damage due to inflammation may result in the mutation of stem cells, leading to tumor development [ 54 ]. It has been reported that NF-κB is activated by YAP1 [ 55 , 56 ]. To determine whether CSCs involved in inflammation can also cause tumor development, we examined the expression of stem cell markers YAP1 and SOX9, and found that their expression in the cancer cells in the CC group was significantly higher than that in the normal cells of the control group.…”
Section: Discussionmentioning
confidence: 99%